2004
DOI: 10.1016/j.jacc.2003.10.049
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin I164T mutation is associated with the metabolic syndrome and coronary artery disease

Abstract: The I164T mutation in the adiponectin gene was a common genetic background associated with the metabolic syndrome and CAD in the Japanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
2
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(107 citation statements)
references
References 35 publications
3
97
2
5
Order By: Relevance
“…However, it has been shown to influence the allelespecific differential expression of the adiponectin gene in human omental adipose tissue [20]. Previous studies have reported increased [8], decreased [21] or unchanged [18] levels of adiponectin in subjects with the T45G variant. In our study, a lower adiponectin level was found in the G carriers, but the result was only significant in the male subjects.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown to influence the allelespecific differential expression of the adiponectin gene in human omental adipose tissue [20]. Previous studies have reported increased [8], decreased [21] or unchanged [18] levels of adiponectin in subjects with the T45G variant. In our study, a lower adiponectin level was found in the G carriers, but the result was only significant in the male subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Males [4] 139.578.2 Females [26] 115.2711.1 Fat % [31] 60.079.1 HOMA index [23] 4.074.2 Fasting glucose (mmol/l) [32] 4.970.6 Fasting insulin (mU/l) [24] 19.5716.8 Leptin (mg/l)…”
Section: Discussionmentioning
confidence: 99%
“…22 Adiponectin serum levels have a heritability of about 30%, 18 indicating that genetic variation within or outside the adiponectin gene could affect the expression of the gene. Several studies have reported an effect on serum adiponectin levels for different single nucleotide polymorphisms (SNPs) in the APM1 gene, 10,12,[17][18][19]23 but to our knowledge only one study has focused on the effect of a genetic marker on the APM1 mRNA expression in omental adipose tissue, reporting increased mRNA levels for the APM1 T94G G-allele. 24 Visceral adipose tissue is more metabolically active than subcutanoeus adipose tissue and is of greater importance for the development of obesity-related complications.…”
Section: Introductionmentioning
confidence: 99%
“…However, SNP+45 GG genotype had no effect on phenotype, that is, on serum adiponectin protein concentrations [35]. Ohashi et al [36] also genotyped gDNA isolated from whole blood specimens procured from 383 coronary artery disease (CAD) individuals and 368 controls ( Table 2, row H). MetS was diagnosed if total cholesterol >5.6 mmol/l, triglycerides >1.69 mmol/l, HDL-cholesterol <1.03 mmol/l, and blood pressure of systolic !140 mm Hg and diastolic !90 mm Hg were present.…”
Section: Forty-two [ 2 5 _ T D $ D I F F ] Snps[ 7 _ T D $ D I F F ]mentioning
confidence: 99%